Analisis Pendekatan Metode TAM Pada Penggunaan Aplikasi E-Commerce - Kersna Minan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The development of the era is also marked by the development of technology. Technological developments are inseparable from human life. Until now, almost all corporate organizations have taken advantage of the developments in internet technology. Utilization of internet technology is an innovation carried out by corporate organizations that can help to improve performance and also business processes in corporate organizations. At this time the business process activities carried out by corporate organizations are virtual or commonly referred to as E-Commerce. The use of e-commerce has now become a very high trend phenomenon. Currently e-commerce is needed to meet the needs of society in the digital era, e-commerce is used as a place to purchase products and even services. Technology Acceptance Model (TAM) is a model used to provide an offer to the acceptance of e-commerce usage and behavior for its users. In this study, a study will be conducted to measure how far e-commerce applications are accepted by the public. And the results show that all hypotheses are accepted, which means it shows that the e-commerce application has been accepted by the community. This is supported by the influence of the variable stimulant of 79.2%.